Cooperative Level among Preschooler During Intravenous Injection Procedures: An Explanative Study - Regina Soares Da Costa Ximenes; Yuni Sufyanti Arief; Elida Ulfiana (Universitas Airlangga, 2020)
Introduction: Hospitalized preschoolers have higher anxiety and fear reactions, especially given intravenous injections that are included in invasive procedures The purpose of this study is to determine the cooperative level of preschool children (4-6 years) during intravenous injection procedure. Methods: The research design used was explanative. The samples numbered 34 children aged 4-6 years who underwent treatment in Dahlia room Mgr Gabriel Manek, SVD Hospital selected by purposive sampling with the variables used namely the cooperative level of preschool children during the intravenous injection procedure. Data was collected using cooperative level observation sheets. Results: The cooperative level of preschool children during the intravenous injection procedure was in the uncooperative category of 31 children (91.1%) while the cooperative category was 3 children (8.9%). Conclusion: The cooperative level of preschool children during the intravenous injection procedure tends to be uncooperative. This is influenced by the age and development of the child and the existence of external support from parents and chaperones during the intravenous procedure. Further research can use this study as data in determining appropriate interventions to improve the cooperative attitude of preschool-aged children during intravenous injection procedures.